Atrakcyjność inwestycyjna Świdnicy w świetle badań ankietowych przedsiębiorców - Kołakowski, Tomasz (Investment Attractiveness of Świdnica in the Results of Businessmen's Questionnaire Audits, 2006)
This article contains the result of an investment attractiveness research which was carried out on companies in Świdnica between 01-25 of March 2005 and presents conclusions of questionnaire audits. Moreover it indicates agents which decide about investment attractiveness of Świdnica and also shows negative aspects, which decrease investment and enterprise development in the city. Furthermore it points to perspectives for individuals and companies which invest and create workplace and local economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 452-462